Entrepreneurial Intentions of Tourism Vocational High School Students in Indonesia and Malaysia - A, Ana; Hurriyati, Ratih; Rostika, Yeyet; Nazeri, & Mohamad (Journal of Technical Education and Training, 2016)
This study aimed to compare the entrepreneurial intention's Tourism Vocational high-school students in Indonesia and Malaysia. The survey design method was used and the Bird's Contexts of Entrepreneurial intentionality model was adopted in the application of the Theory of Planned Behaviour. A total of 228 students from Malaysia (n= 114) and Indonesia (n=114) were recruited as the respondents. Statistical test analysis results using the independent sample t-test showed that there is a statistically significant difference in the average scores of students who come from Indonesia and Malaysia (p< .05) with Malaysian students having higher scores. Also, belief and self-efficacy are found to be the most dominant components associated with the entrepreneurial intentions among students coming from both countries. In conclusion, tourism vocational high school students from Malaysia have stronger entrepreneurial intentions while self-efficacy and belief ply a big role in influencing intention.